Comparative Attenuating Potentials of Pleurotus ostreatus, Non-ionic and Phyto-emulsified Surfactants on Crude oil Impacted Soil and the Hepatotoxicity of Leaf Aqueous Extract of Telfaria occidentalis Harvested from the Attenuated Soil on Wistar Rats - Nwauche, K. T.; Berezi, E. P.; Ugoh, A. I. (European Journal of Applied Sciences, 2024)
This study investigated and compared the hepatotoxicity of aqueous leaf extract of T. occidentalis from crude oil impacted soil and impacted soil amended with Pleurotus ostreatus, non-ionic and phyto-emulsified surfactants. Crude oil highly impacted soil excavated from an oil spill site at Obeche community in Ogba/Egbema/Ndoni Local Government Area of Rivers State, Nigeria was used. Remediation was induced using white rot fungus (Pleurotus ostreatus), phyto-emulsified surfactant (Costus afer stem) and chemical surfactant (Triton x-100) for 60 days after which fresh seeds of T. occidentalis were planted on the soil and allowed to germinate and grow for 6 weeks. Twenty one (21) adult wistar rats weighing between 170-200g were used. They were randomly sorted into seven groups (A-G) of three rats each. After one week of acclimatization, the animals were administered the aqueous leaf extract of T.occidentalis harvested from the soil samples. Liver marker assays and histopathological evaluations were done using standard laboratory methods on the sampled wistar rats. Results from this research revealed a significant difference (p≤ 0.05) in the ALP level when group F (151.33 ± 12.05) is compared with group A (92.66 ± 3.05). Only groups D (74.00 ± 74.48) and G (88.67 ± 3.21) decreased when compared with group A (92.66 ± 3.05). For the AST levels of wistar rats fed with T.occidentalis harvested from cells A to G, only groups B and G are significantly different (p≤ 0.05) when compared with group A. All the amended cells except cell E (41.67 ± 3.78) are observed to be decreased when compared with group A (35.00 ± 4.58). Only groups E, F and G are significantly different (p≤ 0.05) when compared with group A in the ALT levels. Groups B and G are observed to be significantly decreased with values of 18.00 ± 2.64 and 15.67 ± 2.08 respectively when compared with group A (23.00 ± 4.58). Histopathological evaluation of the liver of the wistar rats revealed the presence of congested sinusoid, congested vessels, intraparenchymal inflammation and congested central veins for groups A, C, D and E respectively with mild periportal and intraparenchymal inflammation in groups F and G respectively. Findings from this study revealed that the T.occidentalis leaves harvested from the polluted and amended soil samples caused varying degrees of hepatotoxicity to the rats with only those harvested from group G (Costus afer + Triton x-100) showing no presence of acute hepatotoxicity. The finding therefore indicates that a combined formulation of non-ionic and Costus afer phyto-emulsified surfactants could be a possible remediation pathway in the bioremediation technology.